ANALISIS KETERKAITAN REGIONAL KABUPATEN/KOTA DALAM PEMBENTUKAN KLASTER PENGEMBANGAN EKONOMI WILAYAH PROVINSI ACEH (PENDEKATAN ANALISIS SPASIAL). - Zedi Saputra, Said Muhammad, Sofyan Syahnur. (Jurnal Ilmu Ekonomi : Program Pascasarjana Unsyiah, 2015)
Abstract: Decentralization policy in Aceh does not show a better socio-economic indicator achievement for Aceh. The economic development gap among districts/cities in Aceh Province is also another indicator of not optimal of the decentralization policy. Regional cooperation among districts/cities through Aceh Trade and Distribution Center (ATDC) is one of Aceh Goverment program to improve the Aceh socio-economic state in the next 30 years. This research focus on the development of economic clusters by raising main local product of the district/city which is expected to become a good strategy in supporting Aceh Goverment policy. The reseach analyzes the best regional corelation and cooperation model among the districts/cities through statistical and spatial analysis approach. Based on the average Location Quotient (LQ) index, three sectors of the economy most superior in Aceh are (1) agriculture, livestock, forestry and fisheries (2) electricity, gas and clean water supply (3) services sector. According to Spatial Autocorrelation analysis using key factor of region economic base, LQ index, it is found that spatial correlation pattern among districts/cities in Aceh is very weak. By using Global Moran (Moran’s I) and Local Indicator of Spatial Autocorrelation (LISA) analysis, agriculture, livestock, forestry and fisheries are the only potential sector which have significant correlation among the Aceh districs in term of spactial pattern formation. Keywords : Regional coorperation, economic cluster, Location Quotient (LQ) index, Spatial Autocorrelation, Moran’s I. Abstrak: Kebijakan desentralisasi di Aceh belum menunjukkan indikator capaian sosial ekonomi Aceh yang lebih baik. Terjadinya kesenjangan pembangunan ekonomi antar kabupaten/kota di Provinsi Aceh merupakan indikator lain dari belum optimalnya pemberlakukan kebijakan desentralisasi. Bentuk kerjasama regional antar kabupaten/kota melalui Aceh Trade and Distribution Center (ATDC) merupakan kebijakan Pemerintah Aceh dalam jangka panjang, diharapkan akan mampu untuk memperbaiki kondisi sosial ekonomi Aceh dalam masa 30 tahun mendatang. Dalam penelitian ini dilakukan analisis bentuk keterkaitan antar kabupaten/kota dan pola kerjasama regional yang lebih tepat dan terukur melalui pendekatan statistik dan analisis spasial, dengan menggunakan pembobot indeks LQ. Berdasarkan rata-rata indeks Location Quotient (LQ), 3 sektor ekonomi paling unggul secara rata-rata kabupaten/kota di Aceh adalah (1) sektor pertanian peternakan kehutanan dan perikanan (2) sektor listrik gas dan air bersih dan (3) sektor jasa-jasa. Berdasarkan analisis Spatial Autocorrelation dengan menggunakan pembobot sektor basis ekonomi wilayah, indeks LQ, menunjukkan masih lemahnya pola keterkaitan spasial antar kabupaten/kota di Provinsi Aceh. Hasil analisis Global Moran (Moran’s I) dan hasil analisis Local Indicator of Spatial Autocorrelation (LISA), hanya sektor pertanian peternakan kehutanan dan perikanan yang berpotensi dan signifikan dalam membentuk pola keterkaitan spasial antar kabupaten/kota di Aceh. Kata kunci : Kerjasama regional, Sektor unggulan, Location Quotient, Analisis Spasial, Spatial Autocorrelation, Moran’s I.